Understanding the Variation of Bacteria in Response to Summertime Oxygen Depletion in Water Column of Bohai Sea - Wang, Jing; Guo, Xiaoxiao; Li, Yanying; Song, Guisheng; Zhao, Liang (Frontiers in Microbiology, 2022)
Aiming to reveal the variation of bacteria community under the seasonally formed oxygen depletion in water column of central Bohai Sea, a time-scenario sampling from June to August in 2018 at a twenty-days interval along one inshore-offshore transect was settled. Water samples were collected at surface, middle and bottom layer and then analyzed by high throughput sequencing targeting both 16S rRNA and nosZ genes. Compared to surface and middle water, oxygen depletion occurred at bottom layer in August. In top two layers, Cyanobacteria dominated the bacterial community, while heterotrophic bacteria became dominant in bottom water of Bohai Sea. Based on the time-scenario, distinct community separation was observed before (June and July) and after (August) oxygen depletion. Vertically, strict stratification of bacterial community was stably formed along three sampling layers. As a response to oxygen depletion, the diversity indices of both total bacteria (16S rRNA) and nosZ gene encoded denitrification bacteria all increased, which indicated the intense potential of nitrogen lose when oxygen depleted. Dissolved oxygen (DO) was the key impacting factor on the community composition of total bacteria in June, while nutrient together with DO play important roles in August for both total and denitrifying bacteria. Biotic impact was revealed further by strong correlations showed between Cyanobacteria and heterotrophic bacteria in June from co-occurrence network analysis, which became weak in Au-gust when DO was depleted. This study discovered the variation of bacteria community in oxygen-depleted water with further effort to understand the potential role of denitrifying bacteria under oxygen depletion in Bohai Sea for the first time, which provided insights into the microbial response to the world-wide expanding oxygen depletion and their contributions in the ocean nitrogen cycling.